Analisis Hubungan Sosial antara Komite Audit dan Kantor Akuntan Publik (KAP) terhadap Kualitas Audit - Arif, Viny Amelia; Cheisiviyanny, Charoline (Universitas Negeri Padang, 2023)
This study aims to determine the social relationship between the audit committee and the public accounting firm (KAP) on the audit quality of state-owned companies listed on the Indonesian stock exchange with embeddedness theory. The population of this study is all financial statements of state-owned companies listed on the Indonesia Stock Exchange in the 2016-2019 period with a sample of 60 financial statements using purposive sampling technique, namely considerations. Data analysis used descriptive statistical test and measurement model (Outer Model). The results of data analysis with Adjusted R-squared or simultaneous test show a value of 0.111 or 11.1% which means that social relations affect audit quality by 11.1% which can be categorized as quite low and the remaining 88.9% is influenced by other variables. others outside of this study. This means that social relations have a positive effect on audit quality in state-owned companies listed on the Indonesian stock exchange in the 2016-2019 period.